Pengaruh “Create Bu CaMat” terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Wajib SMA - Nurhayati Nurhayati (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract This research is a classroom action research that aims to determine the effect of math notebooks on learning outcomes. Since learning was carried out online, many changes have occurred, including learning Mathematics. Both in offline and online learning, one of the biggest problems the researcher had was that students needed to remember how to solve various types of problems or skills that had been taught for one year (odd and even semesters). One of the reasons is the habit of only staring at the screen during online learning and not taking good notes on the material provided by the teacher. The new habit of students that has a negative impact is only printing or copying the material that the teacher gives without repeating it. Researchers try to do various things and adapt them to the characteristics of students until they finally find a way to overcome this problem. The way to solve this problem is to use student notebooks in math class. Student notebooks can be used as a central location where students can go back and refresh their memory on each standard being taught without having to be constantly re-explained by the teacher. The effect of applying